NATIONAL DEFENSE MODEL BASED ON DATA SOVEREIGNTY: STRATEGY TO OVERCOME THREATS IN DIGITAL ERA (Economic and Bussiness Faculty, Dr Soetomo University, 2021)
ABSTRACT Threats to national defense and security always develop along with technological advancements. The threat does not only come from the real world which involves physical attacks, but can also come from cyberspace in the form of attacks on the security of state data. The purpose of this research is to develop a national defense model based on the concept of data sovereignty to overcome various threats that come from the digital world. The type of this research is descriptive qualitative with research data in the form of secondary data collected using literature studies and analyzed using qualitative techniques. The model of national defense based on data sovereignty illustrates the components needed to shape national defense. These components consist of policy, institutional, law enforcement, and various other components that contribute to building data sovereignty. Keywords: Data Sovereignty, National Defense and Security, Digital Era, Cyber Threats